Morphological analysis of transgenic tobacco plants overexpressing the Cinnamyl Alcohol Dehydrogenase 2 gene of oil palm / Mohammad Arif Abdul Fataf - Abdul Fataf, Mohammad Arif (Faculty of Plantation and Agrotechnology, 2018)
Oil palm (Elaeis guineensis) is an important crop for edible oil production. Oil palm plantation is threatened by the basal stem rot disease caused by Ganoderma boninense. Several studies showed that lignin is important in plant defense. Cinnamyl Alcohol Dehydrogenase (CAD) played a crucial role in the final step of lignin biosynthetic pathway. Previous studies reported that CAD was involved in lignin biosynthesis and was important in plant defense. To date, there is no report on the study of CAD genes from oil palm. Therefore, this study was conducted to disclose the function of a bona fide CAD gene, namely EgCAD2, from oil palm. Transgenic tobacco plants overexpressing the EgCAD2 developed in previous study were cultivated in vitro for 8 weeks. Morphological analyses were performed to investigate the effects of EgCAD2 overexpression on plant growth and development. Histological analysis was carried out to examine the accumulation of lignin in the stem of transgenic plants. Overexpression of EgCAD2 resulted in alteration in plant morphology. All transgenic tobacco plants showed reduced plant height and internode length. The biomass production also decreased in transgenic plants. The transgenic plants also showed ectopic lignin accumulation in stems compared to wild-type plant. Overall, the results indicated that EgCAD2 plays a role in lignin biosynthesis and involved in plant growth and development. The functions of EgCAD2 gene was identified through transgenic tobacco plants in this study.